Unconventional natural gas development and hospitalizations: evidence from Pennsylvania, United States, 2003–2014. (March 2019) - Denham, A.; Willis, M.; Zavez, A.; Hill, E.
Abstract: Objectives: To examine relationships between short-term and long-term exposures to unconventional natural gas development, commonly known as fracking, and county hospitalization rates for a variety of broad disease categories. Study design: This is an ecological study based on county-level data for Pennsylvania, United States, 2003–2014. Methods: We estimated multivariate regressions with county and year fixed effects, using two 12-year panels: all 67 Pennsylvania counties and 54 counties that are not large metropolitan. Results: After correcting for multiple comparisons, we found a positive association of cumulative well density (per km 2 ) with genitourinary hospitalization rates. When large metropolitan counties were excluded, this relationship persisted, and positive associations of skin-related hospitalization rates with cumulative well count and well density were observed. The association with genitourinary hospitalization rates is driven by females in 20–64 years group, particularly for kidney infections, calculus of ureter, and urinary tract infection. Contemporaneous wells drilled were not significantly associated with hospitalizations after adjustment for multiple comparisons. Conclusions: Our study shows that long-term exposure to unconventional gas development may have an impact on prevalence of hospitalizations for certain diseases in the affected populations and identifies areas of future research on unconventional gas development and health. Highlights: Long-term exposure to unconventional drilling may be harmful to population health. Genitourinary and skin-related hospitalization rates increase with drilling. Healthcare professionals should encourage exposed individuals to seek care early. Research into the causal mechanisms is warranted.